Perbandingan Status Gizi Bayi Umur 0-6 Bulan Dengan Pemberian ASI Eksklusif Dan Susu Formula - Sriwahyuningsih, Ade (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
Exclusive breastfeeding is a term to mention babies who are only given breast milk without other additional food and drinks for babies aged 0 to 6 months. The study aimed to compare the nutritional status of infants aged 0-6 months between exclusive breastfeeding and formula milk in the Monta Health Centre working area in 2023. This research method is a cross-section approach. The population in this study were 335 infants in the Monta Health Centre Working Area. The sample in this study was several babies who were exclusively breastfed, as many as 20, and babies who were given formula milk, as many as 20. The sampling technique used was purposive sampling, and the research instrument looked at KMS. The results of the Mann-Whitney Tests Test obtained a value of p = 0.436; it can be concluded that Ho is accepted, meaning that there is no difference in the nutritional status of infants aged 0-6 months between exclusive breastfeeding and formula milk in the Monta Health Centre working area in 2023, for respondents to be able to give exclusive breastfeeding to their babies who are less than six months old and avoid formula milk as long as breast milk is still sufficient for the baby's needs.